2016
DOI: 10.1095/biolreprod.116.141085
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of Placental Transport of Amino Acids Precedes the Development of Intrauterine Growth Restriction in Maternal Nutrient Restricted Baboons

Abstract: Intrauterine growth restriction (IUGR) is an important risk factor for perinatal complications and adult disease. IUGR is associated with down-regulation of placental amino acid transporter expression and activity at birth. It is unknown whether these changes are a cause or a consequence of human IUGR. We hypothesized that placental amino acid transport capacity is reduced prior to onset of reduced fetal growth in baboons with maternal nutrient restriction (MNR). Pregnant baboons were fed either a control (n ¼… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 47 publications
5
48
0
Order By: Relevance
“…Furthermore, the AA transporter systems L and ASCT2 in the placenta of women with preeclampsia and intrauterine growth restriction (IUGR) are quite different from normal [22], suggesting that AAs may play an important role in the disease mechanism. Lower fetal concentrations of most AAs are observed in the umbilical cord and muscle of IUGR fetuses, compared with normal birth weight fetuses [12,23,24], demonstrating the impaired transport of AAs from the maternal to the fetal circulation in IUGR pregnancies. In our study, we first discovered that most of the AAs decreased in the CHD group, and strong associations were detected between AAs and CHD.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, the AA transporter systems L and ASCT2 in the placenta of women with preeclampsia and intrauterine growth restriction (IUGR) are quite different from normal [22], suggesting that AAs may play an important role in the disease mechanism. Lower fetal concentrations of most AAs are observed in the umbilical cord and muscle of IUGR fetuses, compared with normal birth weight fetuses [12,23,24], demonstrating the impaired transport of AAs from the maternal to the fetal circulation in IUGR pregnancies. In our study, we first discovered that most of the AAs decreased in the CHD group, and strong associations were detected between AAs and CHD.…”
Section: Discussionmentioning
confidence: 97%
“…However, also direct fetal responses to hypoglycemia and reduced amino acids were shown to result in a reduction in mTOR signaling in fetal livers leading to reduced IGF-1 bioavailability and fetal growth restriction [13]. Interestingly, previous animal studies described undernutrition-mediated fetal and placental growth restriction to appear late in gestation after IGF-1/insulin and mTOR placental signaling changed due to early pregnancy undernutrition, showing a clear causality [14]. Similarly, in our present study fetal growth declined most prominently in the third trimester of pregnancy, resulting in smaller newborns and placentas in GB patients.…”
Section: Discussionmentioning
confidence: 99%
“…This has been evidenced by studies in women demonstrating that the activity of key amino acid transport systems A and L is reduced in FGR (Glazier et al 1997;Jansson et al 1998). In addition, animal studies have shown that reductions in placental system A activity precede FGR (Jansson et al 2006;Pantham et al 2016) and that blockade of system A by substrate inhibition results in reduced fetal growth (Cramer et al 2002). Collectively, these studies illustrate the importance of placental amino acid transport for appropriate growth of the fetus and suggest that reductions in amino acid transport may result in FGR.…”
Section: Introductionmentioning
confidence: 96%